Nanostructures for Drug Delivery to the Brain - Martin-Banderas, L.; A. Holgado, M.; L. Venero, J.; Alvarez-Fuentes, J.; Fernandez-Arevalo, M. (Current Medicinal Chemistry, 2011)
This review aims to summarize present approaches employed in delivering drugs to the central nervous system. Changes in blood-brain barrier (BBB) function have been reported in several neurological disorders. A brief description of the blood brain barrier and the main pathologies related to this barrier disfunction are described. Treatments for these disorders are based on several available strategies for delivering drugs into the brain, through circumvention of the BBB, as disruption of the BBB, prodrugs, molecular Trojan horses, among others. Particular attention will be placed on nanocarriers and more specifically on polymeric nanoparticles, which are presented as the most promising strategy for CNS delivery, helping drugs to be targeted more efficiently to the brain. This also allows attacking previously untreatable disorders such as brain tumors and other neurodegenerative diseases. New strategies and technologies commercialized by different pharmaceutical companies are also included.
Keywords: Blood-brain barrier